The Quality Competence of Graduates of Colleges of Education in Palestinian Universities from the Principals and Educational Supervisors' Perspective - Eyad Ali Edagni; noor yhya esleem; Amira Basam ALagha (University of Science and Technology, Yemen, 2018)
The research aimed to identify the quality competence of graduates in colleges of education in Palestinian universities from the principals and educational supervisors' perspective. To achieve the aim, the researchers used the descriptive analytical method, and developed a questionnaire consisting of (28) items, covering three dimensions (personal, cognitive and vocational competence). The population of the study consisted of all principals and educational supervisors working in the educational departments of the ministry of Higher Education in Gaza province in the academic year (2017-2018). The questionnaire was distributed to the randomly selected sample which consisted of (111) respondents. The results showed that the overall assessment degree given by the principals and educational supervisors about the graduates' quality competence in the colleges of education was (high) with a relative weight of (68.52%). The dimensions received these rankings: personal competence (72.34%), cognitive competence (69.63%) and vocational competence (64.34%). Moreover, results showed that there were no statistically significant differences at the level of significance ( ) among the sample assessment degrees about graduates' quality competence according to these variables: gender; profession nature; years of service. The study recommended establishing special centres for teachers' professional development after graduation so as to match graduates' competences to the labour market requirements. Keywords: Quality competence, Colleges of education, Principals, Educational supervisors.